Analisis Biaya Tuberkulosis Paru Kategori Satu Pasien Dewasa di Rumah Sakit di DKI Jakarta - Sari, Ida Diana; Herman, Max Joseph; Susyanty, Andi Leny; Su'udi, Amir (Jurnal Kefarmasian Indonesia, 2018)
In 2014, new TB sufferers in Indonesia reached 324,579. An analysis of the cost aims to calculate the cost of treatment of adult category I pulmonary TB patient and the results obtained. The study was conducted in 5 District General Hospitals in Jakarta in 2014 with new adult TB patients treated as samples. Patients’ and attendants’ characteristics, the costs incurred, and treatment outcome were collected through in-depth interviews at every visit for 6 months. The results showed that 64,5% of patients are men aged between 18-70 years and 80,6% of patients using the BPJS. The number of visits for 6 months is 10 times in average (ideally 16 times). With a utilization of hospital by 10 times, then the total direct costs amount to Rp1.228.867, the total indirect costs are Rp614.670, and the total costs of the overall TB treatment are Rp1.843.537 with an average of Rp307.256 per month. The largest components of direct costs are the cost of the drug and the largest component of indirect costs are the cost of TB patient’s attendants. Drug compliance (68,9%) and being cured (41,9%) of TB patients treated for 6 months are far from expectations.